Disproportionate Minority Contact in Canada: Police and Visible Minority Youth - Fitzgerald, Robin T.; Carrington, Peter J. (Canadian Journal of Criminology and Criminal Justice, 2011)
There is a consensus that some racial groups are over-represented in their contact with the Canadian justice system, but a lack of agreement about possible reasons for this over-representation. The two dominant explanations for disproportionate minority contact (DMC) with the police are differential involvement in crime and differential treatment by the police. Differential treatment may be due to disproportionate possession by minorities of risk factors for police contact or to discriminatory policing. This paper uses data on self-reported delinquency and police contacts from a representative sample of Canadian youth aged 12 to 17 years from the National Longitudinal Study of Children and Youth to test the hypotheses that DMC is due to differential involvement or to differential treatment due to disproportionate risk factors. The results indicate that there was disproportionate minority contact with the police, but no support was found for explanations of DMC in terms of either differential involvement or differential treatment due to risk factors. Distinguishing between youth who report violent delinquency and all other youth, DMC was found only for the non-violent youth; this DMC was also not explained by differential treatment due to risk factors. By eliminating other explanations, the results suggest that racially discriminatory policing may be one explanation for DMC in Canada.